The Effect of Giving Tumpi Tuna Fish Supplementary Food and Biscuit Supplementary Food for Toddlers on Toddler Weight Gain in the Working Area of the Health Center in North Buton Regency - Galih Purnama, Desy; Tasnim, Tasnim; Banudi, La (Waluya The International Science of Health Journal, 2022)
Introduction: Malnutrition is a nutritional problem caused by lack of nutrition all intake both in the short and long term, generally determined by the type of nutrient less consumed by toddlers. The problem of undernutrition can be overcome by means of feeding and health practices for toddlers with the aim of restoring and improving nutrition and forming eating habits of toddlers in adulthood. Method: The type of research used in this study is a quantitative study, namely pre-experimental with a two group pretest-posttest design, with a total sample of 67 toddlers, 35 toddlers tumpi tuna samples and 32 toddler MT biscuit samples carried out for 4 weeks, using an independent t-test. Result: The tumpi tuna group had a greater weight gain than the MT biscuit group for toddlers. Conclusion: Looking at the average increase in body weight of toddlers, giving tumpi tuna isbetter for increasing toddlers' weight than giving MT biscuits to toddlers.